Unity of the church in the New Testament and today - Vischer, Lukas; Luz, Ulrich; Link, Christian (W.B. Eerdmans Pub. Co, 2010)
Introduction ; pt. 1. Difficulties in looking to the New Testament for guidance / Lukas Vischer -- pt. 2. On the way to unity : the community of the church in the New Testament. Jesus ; The beginnings of the church after Easter ; The beginnings of ecclesiology / Ulrich Luz -- The first basic conflict : the church's unity with Israel, Ulrich Luz with Christoph Knoch, Peter Lampe, Andreas Karrer -- The church as the reality of Christ in Paul's thought / Ulrich Luz with Corinna Diestelkamp, Peter Lampe -- Developments in the church after the death of the apostles / Ulrich Luz with Joachim Diestelkamp, Jürg Liechti -- The first ecclesiastical concepts of church unity / Ulrich Luz with Anne Liedtke -- The second basic conflict : church fellowship in the controversy with Christian Gnosticism / Ulrich Luz with Andreas Karrer -- pt. 3. The unity movement : church fellowship in the Oecumene. On the way to unity ; The church's unity with Israel ; Flashpoints of unity ; Conciliar fellowship / Christian Link
Includes index. - Translated from the German